(untitled) (Journal of the College of Education for Women, 2019)
Internal Music is considered as a basis to form music melody that sends rapture andecstasy within ones selves since it occurs directly on ears ( hearing) and since it tightens themeaning to make it penetrating into Heart. It is rhythmic organization occurred inside the textdue to movements of internal sounds since rhythm heavily depends on language andpronunciation. Repetition adds music melody to the poetic text since it increases music inpoetry. The sounds that reoccurred either be letters or words are no more than confirmation.Thus , repetition is artistic phenomena most poets resorted to as to diverse his subjects andmetaphors he depicts in his poetry. The repetition has achieved artistic aesthetics , meaningstrengthening and poetic indication as well. The poets , through repetition, showed theirsufferings by consistently insisting on repetition of some words that expressed their agoniesand panics. This art has included a huge area of poetry volumes ,specially Abdul kareem Al-Qaisi and Yusif the Third , whose poetry appeared reoccurrence and repetition as an artisticphenomena.